In situ polymerization of polypyrrole on cotton fabrics as flexible electrothermal materials. (March 2019) - Xie, Juan; Pan, Wei; Guo, Zheng; Jiao, Shan Shan; Ping Yang, Ling
Polypyrrole/cotton composites have substantial application potential in flexible heating devices due to their flexibility, high conductivity, and thermal stability. In this context, a series of flexible polypyrrole/cotton fabrics were intrinsically prepared using in situ polymerization process with the different Py/FeCl3 concentration ratios. To investigate their structural and morphological properties, thermal stability, tensile strength, conductivity, and heat-generating property, the composite fabrics were subjected to Fourier transform infrared spectroscopy, scanning electron microscopy, X-ray diffraction, thermo-gravimetric analysis, mechanical properties, and resistivity measurements. The results showed that polypyrrole/cotton fabrics exhibited a low resistivity of 0.37 Ω cm. Temperature–time curve showed that temperature of the polypyrrole/cotton fabrics increased very quickly from room temperature to a steady-state maximum temperature of 168.3°C within 3 min at applied voltage of 5 V. Tensile strength of polypyrrole/cotton composites reached to 58 MPa, which far surpassed raw cotton fabrics. Therefore, polypyrrole/cotton fabrics have exhibited high electrical, thermal properties, and mechanical strength, which can be utilized as an ideal flexible heating element.